China : Managing Public Expenditures for Better Results - World Bank (Washington, DC, 2015)
Despite its high economic growth, Chinas public expenditure management faces profound challenges: 1) The retrenchment of the Plan puts more of the burden for the macro and microeconomic policy on the budget. 2) Extra-budgetary funds and quasi-fiscal operations of the banking system undermine fiscal discipline, which contributed to the repeated bouts of inflation. 3) Shifting spending to the Governments priorities is slow, and is in part undone during budget implementation. Over time, this could threaten sustainable growth and equitable growth. 4) While overall social indicators are high, regional disparities remain large. Government services seem overstaffed, which could escalate costs if wages continue to rise. To address these challenges, China needs to reform its public expenditure management. Chinas first priority is restoring fiscal discipline - to delineate a clear budget constraint for every line ministry and unit, and break down the sectoral budgets into organizational budgets. To forge a stronger link between the State Councils policy priorities and the budget, China needs to revamp its budget process. The State should focus on articulating the governments strategic priorities, but leave detailed planning for achieving these priorities to line ministries. Decentralized administration can be a major asset for cost-effective service delivery, if accountability for performance is improved.